The Impact of Karate and Yoga on Children’s Physical Fitness: A 10-Week Intervention Study - Tomasz Rutkowski; Agnieszka Chwałczyńska (Applied Sciences)
This study investigated the effects of a 10-week intervention incorporating karate and yoga on the physical fitness of children aged 10–13. Conducted on a sample of 67 boys, the participants were divided into three groups: karate, yoga, and a control group. Each group underwent physical assessments before and after the intervention, focusing on various fitness components measured by the International Physical Fitness Test (MTSF). The intervention sessions were held twice a week and included warm-up exercises, karate or yoga elements, and cool-down. The results demonstrated significant improvements (p > 0.05) in most physical fitness parameters among the karate and yoga groups in trials: run 50 m, jump, run, endurance, hanging, run, agility, sit-ups, and forward bend. However, there was no significant improvement in hand strength, indicating that the intervention might not have adequately targeted this aspect of fitness. The overall MTSF values changed as follows. For the karate group, the results improved significantly, with the mean increasing by 6.95 ± 0.71. In the yoga group, the results also improved significantly, with the mean increasing by 8.74, while the standard deviation changed by −0.19. In contrast, the control group, which did not participate in additional activities, showed a decline in performance in some areas, notably hand strength and jumping ability. Total MTSF value decreased by −1.05, and the standard deviation changed by 0.71. The findings suggest that both karate and yoga can effectively enhance children’s physical fitness, bringing their performance closer to age-adjusted norms. The study highlights the value of structured physical activity programs in promoting the physical development of children. Although no significant differences were observed between the karate and yoga groups, both interventions contributed similarly to overall fitness improvements. Future research should explore additional factors, such as diet and other physical activities, to provide a more comprehensive understanding of the intervention’s effects.